Waste Water Treatment by Liquid-Solid Adsorption Using Calcined Sand-Clay Mixture Adsorbent - ALmilly, Raghad F.; Hasan, Mohanned H. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
Effluent from incompetent wastewater treatment plants (WWTPs) contains a great variety of pollutants so support water treatments are essential. The present work studies the removal of phosphate species from aqueous solutions by adsorption on to spherical Calcined Sand -Clay mixture (CSCM) used a natural, local and low-cost adsorbent. Batch experiments were performed to estimate removal efficiency of phosphate. The adsorption experiments were carried out as function of pH, dose of adsorbent, initial concentration, temperature and time of adsorption. The efficient removal was accomplished for pH between 10 and 12. The experimental results also showed that the removal of phosphate by (CSCM) was rapid (the % removal 98.9%, 92%, 90%, 89% in 60 min) when the initial phosphate concentrations were at  5, 10, 15, 20 mg/l, respectively at optimum PH 10-12 and optimum dose was 5 gm/200ml.   The adsorption process is time dependent. Thermodynamic studies showed that phosphate adsorption was exothermic. The effect of temperature range of 15-30 °C has been investigated. The results indicated that the temperature significantly affected phosphate adsorption on (CSCM)  adsorbent. Langmuir and Freundlich  isotherms models indicated that both isotherms were proper to describe the adsorption characteristics of (CSCM), with Langmuir being more fit.  Adsorption capacity of phosphate had equal to 0.835 mg phosphorous/g adsorbent. The study reveal that calcined sand-clay mixture is an excellent low cost material for phosphate removal in wastewater treatment process .